Mesenchymal Stem Cell-Derived Extracellular Vesicles for Bone Defect Repair - Dongxue Wang; Hong Cao; Weizhong Hua; Lu Gao; Yu Yuan; Xuchang Zhou; Zhipeng Zeng (Membranes, 2022)
The repair of critical bone defects is a hotspot of orthopedic research. With the development of bone tissue engineering (BTE), there is increasing evidence showing that the combined application of extracellular vesicles (EVs) derived from mesenchymal stem cells (MSCs) (MSC-EVs), especially exosomes, with hydrogels, scaffolds, and other bioactive materials has made great progress, exhibiting a good potential for bone regeneration. Recent studies have found that miRNAs, proteins, and other cargo loaded in EVs are key factors in promoting osteogenesis and angiogenesis. In BTE, the expression profile of the intrinsic cargo of EVs can be changed by modifying the gene expression of MSCs to obtain EVs with enhanced osteogenic activity and ultimately enhance the osteoinductive ability of bone graft materials. However, the current research on MSC-EVs for repairing bone defects is still in its infancy, and the underlying mechanism remains unclear. Therefore, in this review, the effect of bioactive materials such as hydrogels and scaffolds combined with MSC-EVs in repairing bone defects is summarized, and the mechanism of MSC-EVs promoting bone defect repair by delivering active molecules such as internal miRNAs is further elucidated, which provides a theoretical basis and reference for the clinical application of MSC-EVs in repairing bone defects.